Designing An Anterolateral Thigh Flap Using Ultrasound - Visconti, Giuseppe; Bianchi, Alessandro; Hayashi, Akitatsu; Salgarello, Marzia (Journal of Reconstructive Microsurgery, 2021)
Background Preoperative knowledge of themicrovascular anatomy of a patientmay improve safetyand efficacy and reduce morbidity. Today, with the advancement in technology, ultrasound can provide minute details of the structures within the body, which makes this technology very helpful in preoperative evaluation of the traditional perforator flaps as well as thin, superthin, and pure skin perforator flaps.Methods In this article, we will describe the design of one of the most popular perforator flaps, the anterolateral thigh (ALT) flap, using high-frequency and ultrahigh-frequency ultrasound technology.Results Ultrasound technology allows to study preoperatively the ALT donor-site and its microvascular anatomy by using different US modalities in order to provide a virtual surgical plan to the operating surgeon.Conclusion Ultrasound technology allow to expand preoperative knowledge of flap microvascular anatomy and its course within the subcutaneous tissue up to and within the dermis, allowing to select the best perforator for the given reconstruction and the plane of elevation for thin, superthin and pure skin perforator flap.
Keywords: anterolateral thigh flap; thin flap; lateral circumflex femoral artery